2020
DOI: 10.3390/land9090288
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Remotely-Derived Products in Monitoring Gross Primary Production across Arid and Semi-Arid Ecosystems in Northwest China

Abstract: As an important component to quantify the carbon budget, accurate evaluation of terrestrial gross primary production (GPP) is crucial for large-scale applications, especially in dryland ecosystems. Based on the in situ data from six flux sites in northwestern China from 2014 to 2016, this study compares seasonal and interannual dynamics of carbon fluxes between these arid and semi-arid ecosystems and the atmosphere. Meanwhile, the reliability of multiple remotely-derived GPP products in representative drylands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Developed by Li and Xiao [67], this product has a spatial resolution of 0.05° and offers temporal resolutions of 8 days, monthly, and annually. The GOSIF GPP dataset has been validated through comparisons with independent flux tower data, demonstrating high precision and the ability to effectively represent spatiotemporal variations in large-scale GPP [68]. This validation, which considered each biome separately, confirmed the dataset's accuracy in representing photosynthetic activity, particularly in grassland ecosystems.…”
Section: Gosifmentioning
confidence: 75%
“…Developed by Li and Xiao [67], this product has a spatial resolution of 0.05° and offers temporal resolutions of 8 days, monthly, and annually. The GOSIF GPP dataset has been validated through comparisons with independent flux tower data, demonstrating high precision and the ability to effectively represent spatiotemporal variations in large-scale GPP [68]. This validation, which considered each biome separately, confirmed the dataset's accuracy in representing photosynthetic activity, particularly in grassland ecosystems.…”
Section: Gosifmentioning
confidence: 75%
“…More errors arise from the input of FPAR and LUE. Many studies have shown that the FPAR and maximum LUE input by MOD17 are underestimated, making the MOD17 data underestimated compared to other productivity productions (Abdi et al, 2019; Gu et al, 2020; Sjöström et al, 2013; Wang et al, 2017;Zhu et al, 2016; Zhu et al, 2018). Ignoring the saturation led to an overestimation of MOD17 in high FPAR areas (Propastin, Ibrom, Knohl, & Erasmi, 2012; Zhu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the eight subareas are used for geographical zoning rather than vegetation type zoning. The temperate desert region (R1), the temperate grassland region (R2), and the climatic range of the alpine vegetation region on the Qinghai-Tibet Plateau (R3) are restricted by insufficient precipitation or low temperatures and have sparse vegetation and low GPP levels [47][48][49]. Precipitation in the temperate coniferous and deciduous forest mixed forest region (R7) and the cold temperate coniferous forest region (R8) is abundant; vegetation growth in these regions is mainly restricted by temperature and radiation, and the vegetation coverage and GPP are relatively high [50].…”
Section: Study Regionmentioning
confidence: 99%